Effect of transcranial magnetic stimulation in combination with citalopram on patients with post-stroke depression - Zhu, Zhen; Zhu, Hao-Xuan; Jing, Shao-Wei; Li, Xia-Zhen; Yang, Xiao-Yan; Luo, Tu-Nan; Ye, Shuai; Ouyang, Xiao-Chun; Song, Wei-Wei (Frontiers in Human Neuroscience, 2022)
Abstract Background Amelioration of depression in patients with post-stroke depression (PSD) remains challenging. Objective The primary vision was to explore the effect of transcranial magnetic stimulation (TMS) in combination with citalopram on patients with PSD. Methods 100 eligible patients who were diagnosed with PSD were recruited and randomly assigned to the control group (n=50) or the TMS group (n=50). The controls were given conventionally citalopram (10mg/d for consecutive 8 weeks), while, in addition to citalopram, patients in the TMS group were additionally given TMS at 5 Hz once a workday for 8 weeks. The primary outcome was depression status as reflected by 17-item Hamilton Rating Scale for Depression (HAMD-17) score and the second outcome was neuropsychological score determined by Mini-mental State Examination (MMSE) and Wisconsin Card Sorting Test (WCST). Results Patients treated with TMS in combination with citalopram had a drastic decrease in HAMD-17 score during treatment. Bigger changes in HAMD-17 score between baseline and 2 weeks as well as between baseline and 8 weeks in the TMS group were observed (P<0.01). Patients in both groups had increased MMSE scores after treatment. Data of WCST revealed patients with TMS treatment completed more categories (P<0.01) and had a lower RPP in comparison with patients in the control group (P<0.0001). Additionally, TMS in combination with citalopram strikingly improved the MMSE scores in comparison with citalopram. Lastly, there was no striking difference in those side effects between the two groups (P>0.05). Conclusion Our study found TMS in combination with citalopram is conducive to improving depression status and neuropsychological function, which holds great promise for treating PSD.